Potential of Soluble Decellularized Extracellular Matrix for Musculoskeletal Tissue Engineering – Comparison of Various Mesenchymal Tissues - Hanai, Hiroto; Jacob, George; Nakagawa, Shinichi; Tuan, Rocky S.; Nakamura, Norimasa; Shimomura, Kazunori (Frontiers in Cell and Developmental Biology, 2020)
Background: It is well studied that preparations of decellularized extracellular matrix (ECM) obtained from mesenchymal tissues can function as biological scaffolds to regenerate injured musculoskeletal tissues. Previously, we reported that soluble decellularized ECMs derived from meniscal tissue demonstrated excellent biocompatibility and produced meniscal regenerate with native meniscal anatomy and biochemical characteristics. We therefore hypothesized that decellularized mesenchymal tissue ECMs from various mesenchymal tissues should exhibit tissue-specific bioactivity. The purpose of this study was to test this hypothesis using porcine tissues, for potential applications in musculoskeletal tissue engineering. Methods: Nine types of porcine tissue, including cartilage, meniscus, ligament, tendon, muscle, synovium, fat pad, fat and bone, were decellularized using established methods and solubilized. Although the current trend is to develop tissue specific decellularization protocols, we selected a simple standard protocol across all tissues using Triton X-100 and DNase/RNase after mincing to compare the outcome. The content of sulfated glycosaminoglycan (sGAG) and hydroxyproline were quantified to determine the biochemical composition of each tissue. Along with the concentration of several growth factors, known to be involved in tissue repair and/or maturation, including bFGF, IGF-1, VEGF and TGF-β1. The effect of soluble ECMs on cell differentiation was explored by combining them with 3D collagen scaffold culturing human synovium derived mesenchymal stem cells (hSMSCs). Results: The decellularization of each tissue was performed and confirmed both histologically (H&E and DAPI staining) and on the basis of dsDNA quantification. The content of hydroxyproline of each tissue was relatively unchanged during the decellularization process when comparing the native and decellularized tissue. Cartilage and meniscus exhibited a significant decrease in sGAG content. The content of hydroxyproline in meniscus-derived ECM was the highest when compared with other tissues, while sGAG content in cartilage was the highest. Interestingly, a tissue-specific composition of most of the growth factors was measured in each soluble decellularized ECM and specific differentiation potential was particularly evident in cartilage, ligament and bone derived ECMs. Conclusion: In this study, soluble decellularized ECMs exhibited differences based on their tissue of origin and the present results are important going forward in the field of musculoskeletal regeneration therapy.